Replacement Value of Cashew-nut Meal for Soyabean Meal in Finishing Broiler Chickens - Ojewola, G.S.; Okoye, F.C.; Agbakuru, I. (International Journal of Poultry Science, 2004)
In a 5 week feeding trial, cashewnut meal was substituted for Soyabean meal at 0, 25, 50, 75 and 100% and the diets were respectively designated as diets 1, 2, 3, 4 and 5 in a completely randomized design. Body weight changes, feed intake, feed-to-gain ratio and the economics of production were investigated. The feed-to-gain ratio was significantly (p